Persistent community-acquired ochrobactrum anthropi bacteremia in severe dengue infection: a case report - Mohamed Rashidi, Nurul Huda; Azahar, Aizad; Ibrahim, Rosni; Zakariah, Siti Zulaikha (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
We report a rare case of Ochrobactrum anthropi bacteremia in a previously healthy young man who was admitted for severe dengue. O. anthropi is a rarely encountered Gram negative organism which is resistant to commonly used beta-lactam antibiotics. This organism is usually interpreted as a contaminant as it is ubiquitous in the environment. Isolation of this organism upon admission suggested a community-acquired infection. He had persistent bacteremia and had to be treated with a prolonged course of meropenem and ciprofloxacin. This case report highlights the importance of early diagnosis and prompt treatment of this otherwise contaminant as previous reports showed this organism can be an opportunistic pathogen which may lead to severe infection.